Mediating Role of Sustainability Capability in Determining Sustainable Supply Chain Management in Tourism Industry of Thailand - Jermsittiparsert, Kittisak; Joemsittiprasert, Watcharin; Phonwattana, Somsathid (International Journal of Supply Chain Management, 2019)
The current study empirically investigates the factors of sustainable supply chain performance in tourism industry of Thailand. Globally, competition has increased due to involvement of enhanced quality and sustainable practices in business operations including effective supply chain management as it has become one of the prime concerns of firms as it plays vital role in achievement of goals and competitive advantages. The study investigate the relationship between customer awareness as it is one of the crucial factor which needs to be addressed by firms primarily in order to operate in turbulent and highly competitive environment. The customer awareness positively influence SSCM and sustainability capability, similarly competitiveness is investigated with sustainability capability and SSCM, moreover, mediation role was examined between customer awareness, competitiveness and SSCM by sustainability capability. The current study is conducted on tourism industry of Thailand, to determine the effect and influence of customer awareness and competitiveness on sustainability capability and SSCM. The study is unique in determining the mediating role of sustainability capability between independent variable and dependent variable. The analysis of the study suggest that customer awareness influence SSCM, similarly competitiveness also effect SSCM and sustainability capability, moreover mediating effect was also reported and demonstrated in analysis phase of the study by shrinking the effect of independent variables on dependent variables.The study is relevant and investigated the factors related to the development of SSCM and provides guidance to firms to achieve sustainable and continuous improvements in business operations and supply chain of involved stakeholders of Thai tourism industry.